Estudo de citotoxicidade, inflamação e estresse oxidativo em neutrófilos de pacientes com anemia falciforme : influência do tratamento com hidroxiuréia - Pedrosa, Alano Martins (2013)
Falciform Anemia (FA) is a hereditary hemoglobinopathy resulting from a β-globin gene mutation (α2β26 GLU→ VAL) that originates a hemoglobin variant called S (HbS). Its polymerization promotes hemolytic and vaso-occlusive crises (VOC). Nowadays it is known that these reactions are initial FA events that unleash a chain reaction that ends with the generation of oxygen reactive types (ORT) nitric oxide (NO) bioavailability reduction, endothelial lesion, susceptibility to infections and a chronic inflammatory process with direct involvement of neutrophils in the development of such mechanisms. Neutrophils of FA patients, besides developing more rigid, non-deformable structures, also show alterations in the expression of adhesion molecules and the production of cytokines and other mediators that may induce or aggravate clinical events observed in the disease. Hydroxyurea (HU) is the most important improvement in FA treatment and the only medicine with a strong impact on the patients’ quality of life, reducing the number of VOC, hospitalizations and deaths resulting from this condition. However, not much is known about the effects of this medicine on neutrophils and on the functionality of these cells. The present study aimed at investigating cytotoxicity, inflammation and oxidative stress markers in neutrophils of FA patients, as well as the effect of HU treatment over these parameters in hematology ambulatory patients from a university hospital and a blood center, both reference centers in Fortaleza – Ceará. The sample included 101 adult patients of both sexes diagnosed with FA through molecular study and it was divided into two groups: the SS Group – composed of 47 FA patients and the SSHU Group – composed of 54 FA patients under HU treatment. A control Group AA was composed of 50 healthy individuals, voluntary blood donors matched by age and sex. Neutrophils were isolated from whole blood by differential gradient and used to measure test. In toxicity tests carried out, it was observed that HU did not have any cytotoxic effect on patients’ neutrophils, however, was shown a cytoprotective action when compared to group AA and SS patients, with a significant reduction (p<0,001) in lactate dehydrogenase (LDH) levels and an increase in the percentage of viable cells through the metil tiazol tetrazolium (MTT) (p<0,001) and the Trypan Blue exclusion tests. Analyzing neutrophil involvement in inflammatory and oxidative stress processes and in FA, there was a significant elevation in the levels of cytokines and pro-inflammatory markers (TNF-α, MPO) and reduced antiinflammatory interleukin IL-10 group SS, as well as a significant decrease in the activity of antioxidant enzymes (SOD and GSH-Px). Patients under medical treatment with the tested medicine showed similar levels to those found in group AA. Oxidative damage were analyzed through malonaldehyde measurement (MDA), which was evidenced statistical differences between all studied groups (p<0,001), however with a higher average value in the non-treated group of patients. The present study ratified the important role of neutrophils in the inflammatory response promoted by the AF, and shown in an unprecedented way, with the Northeast-BR patients, treatment with HU did not reduce the viability of neutrophils, and modulates its mechanisms pro-inflammatory and pro -oxidants at levels comparable to those of healthy individuals.